The Gnostic Myth of the Pearl: ʽAlā’ al-Dawla al-Simnānī, María Zambrano, Terrence Malick - Gonzalo Carbó, Antoni (Amaltea. Revista de Mitocrítica, 2021)
In the work of the Persian Sufi master ʽAlā’ al-Dawla al-Simnānī (d. 736/1336), «the rare pearl of the Self» is a symbol of spiritual progeniture which has influenced thought Gnostic roots of María Zambrano, who resorts to a similar expression –«rare pearl of total purity»–, due to his readings of the studies of the Islamologists Louis Massignon, Henry Corbin and Frithjof Schuon. In turn, the oriental Gnostic myth of the pearl present in Knight of Cups (2015), a film directed by Terrence Malick, constitutes a clear example of the survival of initiatory tales from the Iranian world in contemporary art.